Penerapan Kompres Ice Gel Pack untuk Penurunan Nyeri Pasien Pasca Operasi Fraktur di Ruang Mawar RSUD Dr. Soehadi Prijonegoro Sragen - Dewi Putri Handayani; Ida Nur Imamah; Yani Indrastuti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
A fracture is an interrupted occurrence of bone continuity determined by the type and extent of the injury. One of his treatments is Open Reduction and Internal Fixation (ORIF). A common problem in post-operative patients is pain, so it requires non-pharmacological implementation of one of which is compressed ice gel pack. To find out the results of ice gel pack compression therapy in post-operative patients. The application was performed with a descriptive method of case study to 2 respondents with a diagnosis of fracture and performed the operation Open Reduction and Internal Fixation (ORIF) performed 6 hours after the operation for 1x within 10-15 minutes. Based on the results of the application already performed there was a decrease in the intensity of pain in postoperative patients. ice gel pack compression therapy can be used as one of the non-pharmacological techniques or independent intervention in post-operative patients in particular on the action Open Reduction and Internal Fixation (ORIF)